Narrating care during the COVID-19 pandemic in a paediatric emergency department. Issue 2 (4th March 2022) - De Vito, Barbara; Castagno, Emanuele; Garrone, Emanuela; Tardivo, Irene; Conti, Alessio; Luciani, Michela; Urbino, Antonio Francesco; Garrino, Lorenza; Dimonte, Valerio
ABSTRACT: The first wave of the COVID-19 pandemic led to high patient loads in many hospitals. However, paediatric emergency departments (EDs) saw a dramatic decrease in admissions, mainly due to the fear of contracting COVID-19 in hospitals. Moreover, paediatric EDs were required to reorganise their services rapidly to deal with the pandemic. We aimed to describe the experiences of healthcare professionals (HPs) working in a paediatric ED in Italy during the first wave of the COVID-19 pandemic through reflective practice. Twenty-six HPs (16 attending paediatricians, 5 residents, 5 paediatric registered nurses) wrote a single, comprehensive text, in which they reflected on their experiences of care during the first wave of the pandemic. The study was framed within narrative medicine as a means for reflective practice. We identified six main themes: the enemy is about to burst in and to sweep us away, raised fences against the enemy, the meaning of time, getting caught in the storm, being and staying in spaces, and the work unrecognisably transformed. Our findings reflect how profoundly HPs' lives changed, inside and outside the hospital, during the first wave of the pandemic. Narration was useful in helping HPs deal with personal issues brought on by the pandemic.